(3Yde GdGLJeGY GdGbJUGOj (B/s - (3YHO GdQMeGf, YHO Gddg eMeOs ((3GdGScfOQjI(B: s (3OGQ GdeYQaI GdLGeYjI(B, s, 2003)
(3fTCI Yde GdGLJeGY GdGbJUGOj hGdGSgGeGJ GdShSjhdhLjI GdJbdjOjI,GdGSgGeGJ GdShSjhdhLjI hJWhQ Yde GdGLJeGY GdGbJUGOj,Cge GdeLGdGJ GdMOjKI aj Yde GdGLJeGY GdGbJUGOjs
(3GdghGeT hGdeQGLY U(B.507s
Keywords: (3GdGLJeGY GdGbJUGOj,Ydes